EFFECT OF TRICHODERMA SPP. AND WATERING FREQUENCY ON GROWTH OF CASHEW (ANACARDIUM OCCIDENTALE L.) SEEDLINGS - Osagie, Joseph Osarumwense; Omere, Esosa Abraham (FUDMA JOURNAL OF SCIENCES, 2025)
Development of environmental friendly seed and soil treatment for high yield is pertinent. Therefore, this study aims to evaluate the effect of Trichoderma spp. and watering frequency on growth of cashew (Anacardium occidentale L.) seedlings in the nursery. This study was laid out in a 4 x 4 factorial arrangement in a Complete Randomized Design (CRD) replicated three times. There were four (4) seed + soil treatments and four (4) watering frequencies. Trichoderma spp. was cultured on Potato Dextrose Agar (PDA) and a Trichoderma seed coating medium was prepared and used to inoculate cashew seeds before sowing. There was no significant interaction between the seed + soil treatments and watering frequency on all plant growth parameters analysed. Watering every 7 days recorded 21 days to emergence, UnSeed + TrSoil had the highest stem girth (2.42cm), UnSeed + UnSoil (11.92) and watering daily (14.08) had the highest number of leaves. TrSeed + TrSoil (21.52cm) and watering daily (22.26cm) had the tallest plants. There was significant difference for effect of watering frequency on root length. TrSeed + UnSoil (11.71g) and watering daily (14.23g) had more fresh weight, while TrSeed + UnSoil (5.60g) and watering every 3 days (4.45g) were the lowest in dry weight. It can be inferred from this study that cashew seedlings will thrive better in soil treated with beneficial microorganisms such as Trichoderma, and also watering daily will have significant influence in plant growth attributes. However, watering daily may not be advised before emergence.